To study and implement inkless binning : in semiconductor industry - Venkatachalam Valliappan (2008)
This thesis introduces a wafer mapping based inkless binning process for wafer sorting to segregate and identify the electrical and functional good dies and reject dies and using the map to pick up the good dies in die attach operation in the semiconductor IC packaging industry.